After the Siege : A Social History of Boston, 1775-1800 - Carr, Jacqueline Barbara, 1954- (Book collections on Project MUSE., 2019)
Drawing on extensive primary sources, including ward tax assessors' Taking Books, church records, census records, birth and marriage records, newspaper accounts, and town directories, Jacqueline Barbara Carr brings to life Boston's remarkable rebirth as a flourishing cosmopolitan city at the dawn of the nineteenth century. She examines this watershed period in the city's social and cultural history from the perspective of the town's ordinary men and women, both white and African American, recreating the determined community of laborers, artisans, tradesmen, mechanics, and seamen who demonstrated an incredible perseverance in reshaping their shattered town and lives. Originally published by Northeastern University Press in 2005. With a new foreword by Jonathan M. Chu.